PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN CANVA MATERI SIKAP BANGGA SEBAGAI BANGSA INDONESIA DI KELAS IV SD - Della Andini; Dinda Yarshal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to determine the development of Learning Media and determine the feasibility of interactive Learning Media assisted by Canva material on being proud as an Indonesian nation in class IV elementary school. This research is R&D (Research and Development). model development in research using the ADDIE model. The subject of this research was the fourth grade teacher at PRIVATE SD PAB 22 Patumbak I. The object of this research was Canva-based interactive learning media regarding the proud attitude of being an Indonesian for fourth grade elementary school students. The feasibility of interactive media assisted by Canva can be seen based on assessments provided by media experts and material experts. Validation results from media experts show a percentage of 96%, which is included in the very valid category. Meanwhile, validation results from material experts obtained a percentage of 95%, also in the very valid category. Meanwhile, the feasibility of interactive media assisted by Canva, which can be seen from the results of the teacher response assessment, obtained a percentage of 94% with the criteria "very good", in other words interactive media assisted by Canva is very suitable for use in learning in fourth grade elementary school. It can be concluded that interactive learning media meets the "Appropriate" criteria for use as learning media.